Peranan Kelompok Informasi Masyarakat dalam Mewujudkan Desa Mandiri di Deli Serdang - Kasiatik Kasiatik; Irwan Nasution (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2015)
This study is aimed at describing and analyzing the Role of Civil Society in Delivering Information Independent Village as well as constraints - constraints faced by the Group of Rural Community information Pasar V Kebun Kelapa Beringin District Deli Serdang.Villagers Pasar V Kebun Kelapa have a low level of education. The survey results revealed that the role of Communities for Information Group (KIM) Village Pasar V Kebun Kelapa until now has not run well. Poverty is one of the fundamental problems at the moment. Community Information group has a role that can be grouped into five activities, namely: As a facilitator for the community, as a partner of the local government, as an absorber and the voice of the people, as pelancaraan flow of information, and as an information terminal for community. By using qualitative analysis methods, namely by way depict or describe in a systematic, factual and accurate information about the facts - facts, nature - the nature and relationship investigated is expected to realize a community that is active and sensitive to information, as well as creating a network of two-way communication media information with connect a community group with other groups in order to empower each other.